(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the theoretical foundations of vitagen educational technology, its application in the humanities, and its practical results. Vitagen technologies serve to support personalized learning by applying life experiences to the learning process in the educational process. The article highlights the importance of developing critical and creative thinking through vitagen technologies, project-based learning, simulation, and life research, as well as the advantages and limitations of these technologies.